Encapsulated bacteria for self-healing in UHP-ECC - Chen, Li Hui (Nanyang Technological University, 2022)
Crack formation in concrete poses a threat to the structural integrity of a building yet it is inevitable and uneconomical to repair using current conventional methods. Bacteria-based self-healing in concrete is an increasingly popular mechanism researched to heal cracks. Due to the high alkalinity of conventional concrete, encapsulation is needed to protect the bacteria to ensure its survival. The encapsulation method this research project focuses on is the dual-capsule system - using Reactive Magnesia Cement (RMC) as capsule material for the bacteria (RMC-B), Portland Cement (PC) and RMC as capsule material for the nutrient (PC-N, RMC-N respectively). Hence, two groups were studied for the evaluation of self-healing performance – RMC-N Group, consisting of RMC-B, RMC-N, and PC as the matrix and PC-N Group, consisting of RMC-B, PC-N, and PC as the matrix. Yeast Extract (YE), the nutrient chosen for the bacteria (Bacillus Cohnii), significantly decreases the strength of the concrete matrix. Hence, carbonation was done to mitigate this problem. The tests done to study the self-healing performance of the system were crack width measurement and water permeability test over 50 wet-dry cycles. Compressive strength tests reported little to no loss of strength in the RMC-N Group which could be due to the carbonation done. However, no strength gain was observed from 7- to 28-day in the PC-N group. The RMC-N Group and PC Group reported full closure at cycle 50 for the crack width range of 0-200um, 85.5% and 97.7% for 200-300um, 84% and 83.1% for 300-550um, respectively. Additionally, Magnesium Oxychloride Cement (MOC) was also a candidate for capsule material due to it having a lower pH tan PC. Bacterial viability test was done on another two groups - MOC and PC as bacteria capsule material to investigate the survivability of the bacteria in the respective materials.